Floristic and phytosociological survey of public squares arbor component in the municipality of Iporá, Goiás, Brazil - Bernardes, Amanda Munielly Alves; Moura, Thamires Marques; Diniz, Vania Sardinha dos Santos; Dias, Maristela Aparecida; Marques, Marlucia (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The urban vegetation is concentrated in the squares and distributed along the streets and avenues. The squares are urban public spaces that encourage socialization and leisure, besides promoting contact of the population with nature. Given its importance, the objective was to evaluate the floristic composition and diversity of tree species present in five squares of the city of Iporá, Goiás, by identifying all individuals with more than 15 cm in diameter and 5 m in height. For this, surveys were conducted in five squares of the city, which were drawn from a previous selection of squares with greater use, aesthetic significance, landscape and representative area. Absolute and relative density, absolute and relative frequency for each species were calculated, as well as the Shannon-Weaver diversity index. It was measured identified 198 tree individuals from 33 species, belonging to 19 botanical families, being Fabaceae and Chrysobalanaceae the most representative. The afforestation of public squares in the municipality of Iporá is represented by most exotic species for the Cerrado, and a medium diversity. Caesalpinia pluviosa and Licania tomentosa are the most frequent species, representing 47,47% of all individuals.